The Role of City Brand in Achieving the Marketing Advantage of the Cities - عطفة ناتاليا; مخول رنا (Latakia University Journal -Engineering Sciences Series, 2021)
Since the beginning of globalizations era, the cities have started to compete each other in order to attract the inhabitants, the tourists, the investments, the events and also the international interest. This race to the top has led the cities to focus on creating “city brand” that could show the uniquity of each city, and that could form an important factor to in light the strengths of each city, which will lead to more competitive advantages. Recently, there are new attempts to use the “city brand” as a tool for “city marketing” in order to promote the city as an aimed distention for people to live, to work or to visit. This research aims to explain the concept of “city brand” in terms of the importance, the types, the procedures and the effectiveness. Also, it aims, through the observation, to study the real practices of some cities which have used the “city brand” as a tool for “city marketing”. Finally, it aims to study the “city brand” of Damascus in the past and what it has reached at the present time, and introduces a city development study to find out its objectives and its relationship to a “city brand” to study its effectiveness. The conclusions of this research have showed that the “city brand” could promise the people with a good quality of life, could meet their needs and could offer for them many advantages. It also could add value to their perception of the city. As a result, “city brand” could show the city as an exclusive place that could be recognized easily. This will help the city to create a marketing value which will lead to attract the inhabitants, the tourists or the investors. It will also lead to affect the local society based on the general objectives that each city has previously set.